Re-examining the bank patronize behavior in Malaysia: a logistic regression approach - Zabri, Zaidi; Abduh, Muhamad (IDOSI Publication, 2013)
This study is aimed at investigating individual as well as bank specific factors affecting bank customers’ decision prior to patronizing a bank. As many as 394 customers from Islamic and conventional banks are involved in the survey and the data collected are analyzed using logistic regression. The results show that working environment, ease of obtaining financing, return on deposits, extensive branch network, professional advice and asset size are the most significant factors influencing their bank patronize decision. Bank management could utilize the findings by re-think the methods to maintain existing customers, attract new customers and eventually to obtain more profit.